ORIENTASI PEMAHAMAN SYARIAT HUMANIS PADA HUKUM POTONG TANGAN: ANALISIS TAFSIR AL-MISBAH DAN AL-AZHAR DI HIMPUNAN MAHASISWA YAYASAN AL-KAHFI - Badru Tamam; Luthfi Zain; Nabilatul Luthfiyah; Nur Arfiyah Febriani; Mulyani Mulyani; Sukataman Sukataman (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Islam, as a religion of mercy for humanity and the entire universe, should demonstrate its existence. This is because Islamic values are universal, touching various aspects of life and are acceptable to all ethnic groups, races, and tribes. Islam highly upholds humanistic Sharia law, embodied in its primary source, the Quran. The concepts of equal access among humans, mutual respect despite differences in background, selfless mutual assistance, and many other life values are gleaned from the Quran. It would certainly be wonderful if these were fully realized in this life. The Quran also upholds laws that apply to the relationship between humans and God. This is closely related to the periodicity of the Quran's revelation. The periodicity of the Quran's revelation itself is divided into two: Makkiyah and Madaniyah. These periods have their own unique characteristics, and the intended audience for the verses is made clearer by this periodicity. Thus, existing interpretations can be adapted to the circumstances and times in which the Quranic verses were revealed. Furthermore, through library research using a sharia deconstruction approach, the author wants to explore the humanist sharia contained through an analysis of the interpretation of Q.S Al-Mā'idah [5]: 38 regarding the law of cutting off hands from two books of interpretation; Tafsir al-Mishbah and Tafsir al-Azhār